ANALISIS KANDUNGAN SULFUR DIOKSIDA (SO2) PADA DAUN ASAM KERANJI (Pitchelobium dulce) DAN KETAPANG (Terminalia catapa L.) DI PT. KIMA, MAKASSAR - Nurhayu Malik (Agriplus, 2014)
This research on Analysis of the content of Sulphur dioxide (SO2) accumulated in Pitchelobium dulce and Terminalia catappa Leaves had been carried out in PT. KIMA of Makassar. The research is aimed at identifying the alloys of Sulphur diokside (SO2) accumulated in Pitchelobium dulce and Terminalia catappa leaves in PT. KIMA, Makassar. The analysis of SO2 content was carried by using of ash analisys was applied to Spectronic -20.  The results of the research suggested for accumulated Sulphur dioxide (SO2), the highest average concentration occurred in west sector with 2,80% for Pitchelobium dulce and 1,60% for Terminalia catappa leaves, whereas the lowest average concentration occurred in the north sector with 0,85% for Pitchelobium dulce leaves and with 0,63% for Terminalia catappa leaves. The capacity of these tho kinds of plants in absorbsing and accumulating pollutans in substantial number with out inducing any physiological change until tha plants died constituted imperortant information, especially in attempt to solve the problem of air pollution occurred in industrial area.   Keywords : SO2, concentration, plant, Pitchelobium dulce, Terminalia catappa.